Progranulin Administration Attenuates β-Amyloid Deposition in the Hippocampus of 5xFAD Mice Through Modulating BACE1 Expression and Microglial Phagocytosis - Guan, Zhangxin; Chen, Zuolong; Fu, Shumei; Dai, Linbin; Shen, Yong (Frontiers in Cellular Neuroscience, 2020)
Loss of function mutations in the progranulin (PGRN) gene is a risk factor for Alzheimer’s disease (AD). Previous works reported that the deficiency of PGRN accelerates β-amyloid (Aβ) accumulation in AD transgenic mouse brains while overexpression of PGRN could restrain disease progression. However, mechanisms of PGRN in protecting against Aβ deposition remains unclear. Here, using 5xFAD AD mouse model, we show that intrahippocampal injection of PGRN protein leads to reduction of Aβ plaques, downregulation of beta-secretase 1 (BACE1), and enhanced microglia Aβ phagocytosis in the mouse hippocampus. Furthermore, PGRN treatment inhibited BACE1 expression in N2a cells and primary culture neurons, and improved the phagocytic capacity of microglia isolated from 5xFAD mouse brains. Collectively, our results provide further evidence that enhancing progranulin could be a promising option for AD therapy.